GOLD PRICE, INFLASI DAN NON PERFORMING LOANS (NPL) TERHADAP PEMBIAYAAN GADAI RAHN - Kristanti Rahman; Eri Kristanto (JURNAL EKONOMI, 2023)
This study aims to analyze the effect of Gold Price (X1), Inflation (X2) and NPL Rate (X3), on Rahn Pawn Financing Distribution (Y) at PT. Pegadaian Syariah in Indonesia. The type of data used is time series secondary data taken from the website harga_emas.org, Bank Indonesia website at www.bi.go.id, Annual report of PT. Pegadaian which is interpolated into monthly data. The data analysis method used in this research is descriptive analysis, classical assumption test and hypothesis testing which is processed using SPSS version 25. Based on the results of the study, the price of gold and NPL have an effect on Rahn pawn financing, but inflation has no effect onRahn pawn financing.